The Impact of Service Quality and Trust on Customer Satisfaction Case Study at PT. Permodalan Nasional Madani (PNM) Melati Mekar - Lasman Eddy Bachtiar; Edward Alezandro Lumban Raja; Trimilda Trimilda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the impact of service quality and trust on customer satisfaction at PT Permodalan Nasional Madani (PNM) Melati Mekar. The researchers used multiple linear regression analysis to analyze the data and tested the hypotheses using the t test and F test with the assistance of SPSS. The findings reveal that service quality has a positive and significant influence on customer satisfaction, as evidenced by the regression coefficient of 0.787 and a t value of 4.782, which is higher than the critical value. Additionally, trust also has a positive and significant impact on customer satisfaction, with a regression coefficient of 0.591 and a t value of 4.056, surpassing the critical value. Furthermore, the F test results demonstrate that customer satisfaction further improves when service quality and trust are combined, with an F count value of 11.520 that exceeds the critical value of 3.19. These results support the statement that both service quality and trust play a crucial role in enhancing customer satisfaction at PNM Melati Mekar.